2012
DOI: 10.1016/j.juro.2011.12.099
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of a Nomogram Using RENAL Nephrometry Score to Predict High Grade Renal Cell Carcinoma

Abstract: We confirm the predictive value of the nomogram using the RENAL nephrometry score to identify high grade renal cell carcinoma in an independent cohort. Further research is required to evaluate its performance using a head-to-head comparison with renal biopsy results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 28 publications
1
29
2
1
Order By: Relevance
“…The area under the curve for these two models was 0.76 and 0.73 respectively, 28 with the latter being validated externally by another group. 29 Even though we found no correlation in our study between Fuhrman grade and RNS, with further development and external validation, there may be a role for RENAL nephrometry in the decision making process when allocating patients to active surveillance or used alongside percutaneous biopsies for histological diagnosis. There are further potential roles for the RNS in renal oncological surgery.…”
contrasting
confidence: 66%
“…The area under the curve for these two models was 0.76 and 0.73 respectively, 28 with the latter being validated externally by another group. 29 Even though we found no correlation in our study between Fuhrman grade and RNS, with further development and external validation, there may be a role for RENAL nephrometry in the decision making process when allocating patients to active surveillance or used alongside percutaneous biopsies for histological diagnosis. There are further potential roles for the RNS in renal oncological surgery.…”
contrasting
confidence: 66%
“…The area under the curve was 73% and 76% for malignancy and high grade, respectively. External validation revealed an area under the curve of 73% for prediction of high-grade disease [40]. Likewise, recent studies showed that higher tumor complexity according to the RENAL score is associated with high-grade disease and clear-cell subtype [41,42].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…This nomogram has been externally validated. 12 The Kutikov nomogram has a predictive capability of malignant potential and tumor grade (high or low) similar to core renal mass biopsy.…”
Section: Nomograms and Risk Assessment Toolsmentioning
confidence: 99%